Medios de comunicación y su impacto en la difusión de información de los problemas y necesidades de los moradores del recinto El Nuevo Mata de Cacao. - López Toaza, Raisa Roxana (2018)
The present research work has as an essential objective to implement a means of communication for the benefit of the residents of the "El Nuevo Mata de Cacao" sector of the Febres Cordero Parish that helps to solve in one way or another the problems that afflict them all. In this research a descriptive methodology was proposed, the inductive, deductive and explanatory method was also used. The techniques of direct observation, surveys and interviews were used, as this means detecting and knowing thoroughly the problem that exists in the residents of the "El Nuevo Mata de Cacao" sector through the statistical tables you will see later on and the same way to think about a proposal that would give a solution to the problem that affects them constantly. The print media, radio and social networks currently play a very important role for society; since nowadays they are mass media of information the same ones that transmit contents of great interest for the citizens, with the purpose that their audience can change their way of thinking, speaking and communicating by offering them every day content that will benefit them.